Occurrence of K1 and K2 serotypes and genotypic characteristics of extended spectrum β-lactamases-producing Klebsiella pneumoniae isolated from selected hospitals in Malaysia - Anuar, Nurul Syazrah; Hazman, Hazmin; Jeyakumar, Sharven Raj; Mohd Desa, Mohd Nasir; Saidi, Hasni Idayu; Masri, Siti Norbaya; Aziz, Nur Afiza; Sulaiman, Nurshahira (Medknow, 2024)
Objective: To determine the distribution, phenotypic and genetic background of extended spectrum β-lactamases (ESBL)-producing Klebsiella (K.) pneumoniae clinical isolates associated with K1 and K2 serotypes in two selected hospitals in Malaysia. Methods: A total of 192 K. pneumoniae isolates were collected and subjected to antibiotic susceptibility, hypermucoviscosity test and multiplex PCR to detect the presence of K1- and K2-serotype associated genes. Multilocus sequence typing (MLST) was performed on ESBL-producing K. pneumoniae isolates presented with K1 and K2 serotypes, followed by phylogenetic analysis. Results: A total of 87 out of 192 (45.3%) of the K. pneumoniae isolates collected were ESBL producers. However, only 8.3% (16/192) and 10.9% (21/192) of the total isolates were detected to carry K1- and K2-serotype associated genes, respectively. Statistical analysis showed that K1 and K2 capsular serotypes were not significantly associated with ESBL phenotype (P=0.196). However, they were significantly associated with hypervirulent, as demonstrated by the positive string test (P<0.001). MLST analysis revealed that ST23 as the predominant sequence type (ST) in the K1 serotype, while the ST in the K2 serotype is more diverse. Conclusions: Although the occurrence of ESBL-producing isolates among the hypervirulent strains was low, their coexistence warrants the need for continuous surveillance. MLST showed that these isolates were genetically heterogeneous.